KEAJAIBAN HARI TUHAN: TAFSIR KITAB MALEAKHI 4:1-6 - Pondi, Diva Yostina (Sekolah Tinggi Teologi Imauel Pacet, 2024)
Abstract : The prophecy of Malachi 4:1-6 contains important eschatological themes surrounding the day of the Lord and its implications for believers. This article aims to explore the theological meaning behind this prophecy. With an analytical approach to Bible interpretation and qualitative methods by collecting data from literature such as books, journals and the Bible. The goal is to gain a deep understanding of the topic being researched, namely the concept of the day of the Lord and eschatological elements such as Divine judgment, the salvation of the redeemed, and the reality of the Kingdom of God. The concept of the